2023
DOI: 10.3389/fmolb.2023.1235160
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic and lipidomic analyses reveal lipid dysregulation in the plasma of acute leukemia patients

Cindy Arévalo,
Laura Rojas,
Mary Santamaria
et al.

Abstract: Acute leukemias (AL) are aggressive neoplasms with high mortality rates. Metabolomics and oxidative status have emerged as important tools to identify new biomarkers with clinical utility. To identify the metabolic differences between healthy individuals (HI) and patients with AL, a multiplatform untargeted metabolomic and lipidomic approach was conducted using liquid and gas chromatography coupled with quadrupole-time-of-flight mass spectrometry (LC-QTOF-MS or GC-QTOF-MS). Additionally, the total antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Our proposed metabolic biomarkers (threonine, malic acid, proline, glycine, succinic acid, lactic acid, 3-hydroxybutyrate, alanine, and glutamic acid) are conserved between mice and humans and play fundamental roles in central metabolic pathways that are highly conserved across mammalian species (Warburg effect, TCA cycle, and amino acid metabolism). Indeed, a recent study using untargeted metabolomics between ALL patients and healthy donors [ 24 ] found alterations in many pathways in common with us, suggesting that it is likely that the differences we found using a murine model of T-ALL could apply to a human setting.…”
Section: Discussionmentioning
confidence: 62%
“…Our proposed metabolic biomarkers (threonine, malic acid, proline, glycine, succinic acid, lactic acid, 3-hydroxybutyrate, alanine, and glutamic acid) are conserved between mice and humans and play fundamental roles in central metabolic pathways that are highly conserved across mammalian species (Warburg effect, TCA cycle, and amino acid metabolism). Indeed, a recent study using untargeted metabolomics between ALL patients and healthy donors [ 24 ] found alterations in many pathways in common with us, suggesting that it is likely that the differences we found using a murine model of T-ALL could apply to a human setting.…”
Section: Discussionmentioning
confidence: 62%